Comparative Study of Traditional Single-Needle Electrospinning and Novel Spiral-Vane Electrospinning: Influence on the Properties of Poly(caprolactone)/Gelatin Nanofiber Membranes - Xu, Qi; Liu, Wei; Yi, Bingcheng (Frontiers in Bioengineering and Biotechnology, 2022)
Spiral-vane electrospinning (SVE), a novel needleless electrospinning, was proven effective in obtaining high-throughput production of nanofibers. However, the properties of the electrospun nanofibers produced by SVE remain relatively underexplored, especially in comparison with those made by traditional single-needle electrospinning (SNE). Hence, for the comparative study of SNE and SVE in this study, the difference in the preparation mechanism was first analyzed using numerical simulation, followed by the experimental analysis of the effects of spinneret types on the quality and biocompatibility of electrospun poly(caprolactone)/gelatin (PCL/Gel) nanofibers. The values predicted by the electric field results were consistent with the experimental data, showing that the PCL/Gel nanofibers prepared by SVE have higher yields than SNE. Although the different spinnerets (i.e., needle and spiral vane) had little effect on the surface chemistry, thermal stability, and composition of the PCL/Gel nanofibers, they had great effects on the fiber diameter distribution and mechanical properties in which SVE-electrospun nanofibers have the wider diameter distribution and higher softness. Furthermore, the SVE-electrospun nanofibers were also proven to exhibit good biocompatibility for cell growth of human adipose-derived stem cells (hADSCs) and cell–fiber interactions. Summarily, compared to the traditional SNE, SVE-electrospun nanofibers exhibited many merits including high-throughput yield, good air permeability, and compliance, which provide a facile and effective platform for the improvement of nanofiber applications in biomedical fields (e.g., tissue engineering, cosmetic, and medical textiles).